The effect of online nutrition and lifestyle education on body image dissatisfaction, body mass index, and disordered eating among female university undergraduate students in Lagos, Nigeria - Foluke Adenike Olatona; Annette Van Onselen; Unathi Kolanisi (The South African Journal of Clinical Nutrition)
Background: Despite the increasing prevalence of body image dissatisfaction (BID), the effect of social media on body image (BI) among undergraduates, and the prohibitive cost of traditional health education interventions, little is known about the effectiveness of online lifestyle interventions to address BI, body mass index (BMI) and disordered eating (DE).Objectives: This study aimed to assess the effect of an online nutrition and lifestyle intervention programme on BI, BMI, and DE among female undergraduate students in Lagos.Methods: A quasi-experimental study involving intervention and control groups was undertaken. A total of 1 182 students (590 students from intervention and 592 from control) responded to follow-up out of 2 015 who completed the pre-intervention survey. Data were collected using pre-tested semi-structured self-administered questionnaires. Pulver's Figure Rating Scale was used to determine BID. BMI was calculated following standard procedures. DE was assessed using the Eating Attitudes Test (EAT-26). The intervention programme was implemented through online learning and social media for 12 weeks. SPSS (version 25) was used for analysis. The association between variables was determined using chi-square while the level of significance was set at p = < 0.05.Results: The intervention reduced BID, BMI and DE among the intervention group significantly (p < 0.05) compared with the control group. Although the highest proportion of students with BID was among the overweight/obese, many students who were normal weight (49.2%) or underweight (47.3%) were dissatisfied.Conclusion: Online nutrition and lifestyle education could effectively reduce BI, BMI and DE among female undergraduate students in Lagos, Nigeria.